Pastoral landscapes learn to paint panoramic vistas and colorful flora step by step - Glover, David Lloyd 1949- (California, usa Walter Foster Publishing, 2014)
mastering composition - achieving depth suggesting light - rendering foliage
13
Keywords: Acrylic -- painting -- Technique; Landscape painting -- Technique